PROFESIONALISME GURU DI ERA REVOLUSI INDUSTRI 4.0 - Nurkholis, M. Anwar; Badawi, Badawi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Revolution 4.0 requires teachers to be professional in the world of education. The role of teachers in the world of education is very urgent, because the condition of learning is the existence of a teacher. As teachers who live or are in the current global era, we are required to be creative and master technology so that it is not left behind by the current era. It is undeniable that the era of globalization requires us to be active, creative, master technology. If we cannot keep up with the current development of modern times, then we will be left behind by others.